2021
DOI: 10.1111/nmo.14236
|View full text |Cite
|
Sign up to set email alerts
|

A survey of functional dyspepsia in 361,360 individuals: Phenotypic and genetic cross‐disease analyses

Abstract: Background Functional dyspepsia (FD) is a common gastrointestinal condition of poorly understood pathophysiology. While symptoms’ overlap with other conditions may indicate common pathogenetic mechanisms, genetic predisposition is suspected but has not been adequately investigated. Methods Using healthcare, questionnaire, and genetic data from three large population‐based biobanks (UK Biobank, EGCUT, and MGI), we surveyed FD comorbidities, heritability, and genetic correlations across a wide spectrum of condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“… 51 106 A more recent large-scale survey of comorbidity and genetic predisposition in FD confirmed a weak heritability of only 5%, but also suggested considerable clinical and genetic overlap with other conditions, including other gastrointestinal disorders, such as IBS and gastro-oesophageal reflux disease (GORD), personality traits, mood disorders and, interestingly, non-gastrointestinal diseases, such as rheumatological disorders and, to a lesser extent, cardiovascular disease. 106 This study also suggested genes likely to play a role in FD, namely those involved in synaptic transmission and neuroplasticity, and gastrointestinal development and integrity. However, additional large-scale studies are required to confirm these findings and identify other potential gene candidates.…”
Section: Pathophysiologymentioning
confidence: 60%
“… 51 106 A more recent large-scale survey of comorbidity and genetic predisposition in FD confirmed a weak heritability of only 5%, but also suggested considerable clinical and genetic overlap with other conditions, including other gastrointestinal disorders, such as IBS and gastro-oesophageal reflux disease (GORD), personality traits, mood disorders and, interestingly, non-gastrointestinal diseases, such as rheumatological disorders and, to a lesser extent, cardiovascular disease. 106 This study also suggested genes likely to play a role in FD, namely those involved in synaptic transmission and neuroplasticity, and gastrointestinal development and integrity. However, additional large-scale studies are required to confirm these findings and identify other potential gene candidates.…”
Section: Pathophysiologymentioning
confidence: 60%
“…This reinforces the capacity to subgroup cases based on diabetes risk score. This is presented in the Supplementary Material Figure 2 Additionally, we explored the frequencies of previously reported variants in a functional dyspepsia GWAS 11 . Two variants previously reported came out as nominally significant: rs2595968 (NFASC p -value<0.004) and rs17597505 ( p -value<0.03).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study with a large sample size reported FD and other gastrointestinal disorders shares several commonalities in a wide spectrum of pathophysiology, which increases the difficulty of treatment against a specific disease ( 15 ). Compared to a global exploration, it is more important to profile the comprehensive features locally.…”
Section: Discussionmentioning
confidence: 99%